2015
DOI: 10.1103/physrevd.92.024031
|View full text |Cite
|
Sign up to set email alerts
|

First law and a variational principle for static asymptotically Randall-Sundrum black holes

Abstract: We give a new, intrinsic, mass definition for spacetimes asymptotic to the Randall-Sundrum braneworld models, RS1 and RS2. For this mass, we prove a first law for static black holes, including variations of the bulk cosmological constant, brane tensions, and RS1 interbrane distance. Our first law defines a thermodynamic volume and a gravitational tension that are braneworld analogs of the corresponding quantities in asymptotically AdS black hole spacetimes and asymptotically flat compactifications, respectivel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 49 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…In this paper, we applied our variational principle [18] to initial data for small asymptotically RS2 black holes, and found two static black holes. We showed that the well known static black hole on the brane is stable against translations transverse to the brane, and has a large binding energy to the brane due to the brane's orbifold symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we applied our variational principle [18] to initial data for small asymptotically RS2 black holes, and found two static black holes. We showed that the well known static black hole on the brane is stable against translations transverse to the brane, and has a large binding energy to the brane due to the brane's orbifold symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Here we formulate the initial data for small initially static black holes in RS2. As described in [18], this amounts to solving the constraint R = 2Λ, where R is the Ricci scalar of the spatial metric h ab . The spatial geometry can be visualized as a conventional embedding diagram [20,21] with two asymptotically RS2 regions (instead of asymptotically flat regions), connected by a bridge.…”
Section: Formulation Of the Initial Datamentioning
confidence: 99%
See 1 more Smart Citation
“…If all of the black hole charges have the same sign, then our extremum principle is a type of variational principle, and augments a list of existing principles [6][7][8] that interpret static black holes (here, the static Hartle-Hawking solution) as extrema of total energy. Our results are also consistent with the supersymmetric BPS energy minimum (E = |Q|) of [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our extremum principle (2) adds the case of charged black holes to these earlier variational principles [6][7][8] and identifies the static Hartle-Hawking solution as its energy extremum. In contrast to [6][7][8], in this paper, the number N of black holes that we consider is arbitrary, and our energy extremum varies (rather than holds fixed) the black hole areas.…”
Section: Introductionmentioning
confidence: 99%